Simultaneous integrated boost within the lymphatic drainage system in breast cancer: A single center study on toxicity and oncologic outcome - Klusen, Sophie T.; Peiler, Antonia; Schmidt, Georg P.; Kiechle, Marion E.; Muench, Stefan; Asadpour, Rebecca; Combs, Stephanie E.; Borm, Kai J. (Frontiers in Oncology, 2023)
BACKGROUND AND PURPOSE In breast cancer patients, the increasing de-escalation of axillary surgery and the improving resolution of diagnostic imaging results in a more frequent detection of residual, radiographically suspect lymph nodes (sLN) after surgery. If resection of the remaining suspect lymph nodes is not feasible, a simultaneous boost to the lymph node metastases (LN-SIB) can be applied. However, literature lacks data regarding the outcome and safety of this technique. MATERIALS AND METHODS: We included 48 patients with breast cancer and sLN in the current study. All patients received a LN-SIB. The median dose to the breast or chest wall and the lymph node system was 50.4 Gy in 28 fractions. The median dose of the LN-SIB was 58.8 Gy / 2.1 Gy (56-63 Gy / 2-2.25 Gy). The brachial plexus was contoured in every case and the dose within the plexus PRV (+0.3-0.5mm) was limited to an EQD2 of 59 Gy. All patients received structured radiooncological and gynecological follow-up by clinically experienced physicians. Radiooncological follow-ups were at baseline, 6 weeks, 3 months, 6 months and subsequent annually after irradiation. RESULTS: The median follow-up time was 557 days and ranged from 41 to 3373 days. Overall, 28 patients developed I°, 18 patients II° and 2 patients III° acute toxicity. There were no severe late side effects (≥ III°) observed during the follow-up period. The most frequent chronic side effect was fatigue. One patient (2.1 %) developed pain and mild paresthesia in the ipsilateral arm indicating brachial plexopathy. After a follow-up of 557 days (41 to 3373 days), in 8 patients a recurrence was observed (16.7%). In 4 patients the recurrence involved the regional lymph node system. Hence, local control after a median FU of 557 days was 91.6 %. CONCLUSION: In the current study, LN-SIB was associated with acceptable toxicity and reasonable locoregional control. LN-SIB-irradiation can be considered as a potential treatment option if re-resection of sLN after initial surgery is not feasible. Patients receiving a LN-SIB need to be informed about a higher risk of brachial plexopathy, in particular if a large volume is included in the LN-SIB.